Environmental sensitivity and cardiac vagal tone as moderators of the relationship between family support and well-being in low SES children: An exploratory study. (September 2021) - Moscardino, Ughetta; Scrimin, Sara; Lionetti, Francesca; Pluess, Michael
This cross-sectional study explored whether the association between perceived family support and child well-being was moderated by the individual trait of Environmental Sensitivity (the ability to register, process, and respond to stimuli) and cardiac vagal tone (CVT, an index of self-regulation) in a sample of children living in socioeconomically disadvantaged families. Participating children ( N = 131, M age = 7.20 years, 47% boys) were individually interviewed about the support received within the family as well as their physical and emotional well-being. Children's sensitivity was assessed via a series of behavioral tasks, and CVT was recorded at rest. Hierarchical cluster analysis on the behavioral items yielded three sensitivity groups: "Low sensitive" (43%), "Moderately sensitive" (33%), and "Highly sensitive" (24%). The three groups of children did not differ in baseline CVT. However, linear regression analyses revealed that at low and average levels of family support, highly sensitive children with higher resting CVT reported better well-being than those with low resting CVT, whereas no effect was observed among children in the other two groups. In the context of high family support, children reported high levels of well-being irrespective of their levels of vagal activity or sensitivity. The findings suggest that among low SES families, when children experience a poorly supportive family environment and are highly sensitive to negative experiences, having a higher resting CVT may confer an advantage in terms of well-being. Implications for theory and practice are discussed.